Spiritual Power and Everyday Lives: James Bay Cree Shaking Tent Performers and Their Audiences. - Feit, Harvey A. (Hokkaido University Press., 1997)
I focus on the discourses and messages conveyed to the attendees at two shaking tent ceremonies among James Bay Cree in the 1960s. I explore some of the meanings such ceremonies convey through oral dialogue, through ritual symbols, and through the social relationships which are created and acknowledged by the ceremony. Often the dialogues of those who speak in the ceremony are about the spiritual powers they have. They also explore if and how these differences with other people are acceptable. The statements, as well as the symbolic structure of the performance itself, emphasize the services which the those active in the ceremony perform for the community. They also stress the obligations they undertake to spirit powers. They also make light of the differences, and joke about them. I suggest that the dialogues both claim a special access to powerful knowledge, and they point to the power of everyday access to spiritual knowledge that is available to all people. I approach the two ceremonies through the lens of what I learned from talking with many James Bay Cree people, not only those involved with ceremonies, about the ordinariness of everyday lives lived in spiritual awareness.
The recording of a 1969 shaking tent ceremony in the Waswanipi region was a joint project with the family of the Late Andrew, Joseph, Jr. and Eva Ottereyes. Our work together on this and other projects extended over the following five decades. It was an extraordinary gift for me to have been a part of it. Each of us envisaged reasons for recording the ceremony, for some it was for younger family members, for some for future generations of Cree, for some for the value of the knowledge for wider audiences. This article was a part of that process. In addition to the Ottereyes family, publishing about the ceremony in 1994 and 1997 became a continuing occasion to learn from the comments of other Waswanipi Cree people, among whom I want to specially acknowledge Diane Ottereyes Reid, Hattie Kitchen, and Kevin Brousseau. From what they shared with me I would not now use terms like ‘performance,’ ‘performer’ and ‘audience,’ among others in the article, because of the ambiguities or errors those terms convey in English. I am also aware now that the English text of the ceremony which is presented here is not the same as a linguists’ transcription-translation, but more an English translation-paraphrasing-commentary on the often difficult and sometimes undecipherable Cree text. I also want to also acknowledge valuable discussions about ceremonies with Richard J. Preston, Colin H. Scott, Brian Craik, and Richard Slobodin.
Keywords: Shaking Tent Ceremony; Spirituality; Everyday Life; Equality and Inequality